1994
DOI: 10.1271/bbb.58.18
|View full text |Cite
|
Sign up to set email alerts
|

Desmutagenicity of Melanoidins against Various Kinds of Mutagens and Activated Mutagens

Abstract: The desmutagenic activities of low-molecular weight melanoidins (LM-MEL, MW 500-1000) and nondialyzable melanoidins (ND-MEL, MW above 1000) prepared from a glucose-glycine reaction system were examined by Ames' test on such mutagens/carcinogens as nitro or amino compounds of aromatics or heterocycles, azo compounds, nitroso compounds, and epoxides. ND-MEL and LM-MEL exhibited a desmutagenic activity of 25-75% against mutagenic aromatic or heterocyclic compounds such as aflatoxin B1, B[α]P, 2-aminofluorene, 4-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…, Nicoli et al (1997), Manzocco et al (2001), Morales (2005), , Rufián-Henares and Morales (2007a), Daglia et al (2000), Cioroi (2000), Steinhart et al (2001), Borrelli et al (2002aBorrelli et al ( , 2002b, Wagner et al (2002), Morales and Jimenez-Perez (2004), Esposito et al (2003), Martín et al (2009) Desmutagenic and antitumor activity Kato et al (1985), Lee et al (1994), Inhibition of nitrosamine formation Kato et al (1987) Inhibition of angiotensin-I converting enzyme Rufián-Henares and Morales (2007a, b) Antimicrobial activity Stecchini et al (1991), Daglia et al (1994), Rufián-Henares and Morales …”
Section: Antioxidant Activitymentioning
confidence: 99%
“…, Nicoli et al (1997), Manzocco et al (2001), Morales (2005), , Rufián-Henares and Morales (2007a), Daglia et al (2000), Cioroi (2000), Steinhart et al (2001), Borrelli et al (2002aBorrelli et al ( , 2002b, Wagner et al (2002), Morales and Jimenez-Perez (2004), Esposito et al (2003), Martín et al (2009) Desmutagenic and antitumor activity Kato et al (1985), Lee et al (1994), Inhibition of nitrosamine formation Kato et al (1987) Inhibition of angiotensin-I converting enzyme Rufián-Henares and Morales (2007a, b) Antimicrobial activity Stecchini et al (1991), Daglia et al (1994), Rufián-Henares and Morales …”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Toxicological activities of MRPs that involve reduced nutritional quality,8 derived mutagenicity,9–11 and cytotoxicity12,13 have also been reported. In contrast, studies have shown MRPs to have potential anticarcinogenic and/or antimutagenic effects against various toxic compounds, such as heterocyclic amines,14 B(a)P, aflatoxin B 1 , epoxides, and nitroso‐ and azo‐compounds 15,16. These apparently beneficial bioactive properties are potentially the result of free radical scavenging or metal chelating activities that characterize an important biological role for MR antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…They absorb or inactivate various radicals likeиOH , O 2 -, H 2 O 2 ( Hayase 1996;1997) and chemical compounds like Trp-P-2, a mutagen (Lee et al, 1994). Peroxynitrite, a reaction product of NO and superoxide, is known to be a stronger DNA damaging agent than NO itself.…”
Section: Resultsmentioning
confidence: 99%
“…They are contained in many foods such as soy sauce, miso, roasted coffee etc., and play an important role in adding desirable flavor and color to food. In addition to making food more desirable, there have been many reports about their physiological functions , such as promotion of faecal bacterial growth (Ames et al, 1999), suppression of tumor cell growth (Kamei et al, 1997), inhibition of digestive enzymes (Hirano et al, 1994(Hirano et al, , 1996, antioxidative activity (Chuyen et al, 1998), and antimutagenic activity (Lee et al, 1994). We examined DNA damage-protecting activities of melanoidins using the comet assay, a single cell gel electrophoresis assay which has been used to detect the genotoxic effect of irradiation of various foods (Cerda et al, 1997;Singh, 1988).…”
mentioning
confidence: 99%